Eyelid Thread-lifting Treatment for Periocular Infantile Hemangioma in an Extremely Premature Low-birth-weight Infant. Issue 8 (August 2019) - Kurachi, Ayana; Ozaki, Mine; Ihara, Aki; Eto, Hitomi; Takushima, Akihiko
Abstract : Summary: Periocular infantile hemangioma (IH) sometimes hinders proper eye opening and limits the visual field. Even short-term deprivation of hemilateral vision may cause amblyopia in infants during the visually sensitive period and, thus, necessitates prompt treatment. Propranolol is a commonly known remedy for IH, though it may not act sufficiently to rapidly resolve a vision-threatening critical condition in an infant. Low birth weight is a significant risk factor for IH incidence. Despite the high incidence, evidence-based treatment for IH in preterm infants has not been established. This report describes periocular IH of an extremely premature low-birth-weight infant (body weight: 526 g) whose lesion showed no reduction after oral administration of propranolol for 2 weeks but was successfully treated by topical steroid injection and eyelid thread-lifting management, with no eventual visual impairment.